Consumer Insights on Augmented Reality Marketing in Retail Food Industry: A Grounded Theory Approach - Huang, Lijia (2025)
Although the rapid development of augmented reality (AR) technology has garnered the interest of scholars, research on how to build AR marketing in the retail food industry from the customers’ perspective is lacking. However, it is crucial to ensure that future AR marketing strategies align with the expectations and requirements of customers. Three major research questions were developed and suggested: How does AR marketing influence consumer purchasing decisions within the retail food industry? What key factors contribute to consumer engagement and satisfaction with AR marketing in the retail food sector? How do consumers perceive the long-term benefits and potential challenges of AR marketing in the retail food industry? This thesis employs a grounded theory approach. The data were collected using a mix of qualitative methods such as focus groups and semi-structured in-depth interviews with 27 participants within 18 months. Convenient and purposive sampling techniques were used to select and recruit the participants. The data were analyzed using NVivo Mac 1.7.1. The findings revealed that informativeness, personalization & customization, and consumer data security are key variables for meeting customers’ expectations when applying AR marketing in the retail food industry. Moreover, information automation can help generate a sustainable positive feedback loop. This thesis makes a theoretical contribution by exploring emerging marketing applications within the retail food industry. It evaluates the effectiveness of AR marketing from the consumer’s perspective and identifies strategic approaches that align with consumer preferences. Furthermore, it examines the impact of AR on consumer-brand relationships and highlights key elements of AR application design that enhance user experience. Lastly, it facilitates the development of a robust theoretical framework based on primary data. Overall, this thesis provides valuable guidance for implementing AR marketing in the retail food industry.